STUDY OF SHALLOW GROUNDWATER CHARACTERISTICS IN SANGIRAN DOME, KALIJAMBE DISTRICT - Cikal Lembayu; Chatarina Muryani; Setya Nugraha (GeoEco, 2020)
The purpose of this study are knowing the shallow groundwater flow patterns and characteristics in the Sangiran Dome. This research uses descriptive qualitative method, carried out with survey methods that are analyzed with spatial approach. Unit analysis of this studied is the landform unit the result of a overlay between the Geological’s Map,  Genesis’s Process, and Slope’s Map, the result is 15 landform units. Data analysis techniques is to determine the pattern of shallow groundwater flow using the three point problem method. Data analysis is to determine the characteristics of groundwater by using the parameters of power oh Hydrogen (pH), temperature, and Electrical Conductivity (DHL). The results of this study are the shallow groundwater flow patterns in the Sangiran Dome are concentrated in the Kalibeng Formation, the diffuse flow patterns are in the Pucangan Formation and irregular flow patterns are found in Kabuh Formation and Noropuro. The characteristics of shallow groundwater in the Sangiran Dome, based on pH. Neutral classification are found in the Notopuro Formation, the lower Pucangan Formation; base pH classification found in Kabuh Formation, upper Pucangan Formation, and Kalibeng Formation; acidic pH classification is found in the Notopuro Formation. The low DHL classification is found in Notopuro Formation, Kabuh Formation, and Pucangan Formation while the moderate DHL classification is in the Kalibeng Formation.